Optimized bentonite clay adsorbents for methylene blue removal - Hamad, Hamad Noori; Idrus, Syazwani; Yusuf, Badronnisa; Jamali, Nur Syakina; Ahsan, Amimul; Suhartini, Sri; Abdul Wahab, Abdul Malek (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This study addresses the urgent need for effective water treatment methods by synthesizing and characterizing activated bentonite clay (ABC) adsorbents to remove methylene blue (MB) from aqueous solutions efficiently. Conventional adsorbents often exhibit limitations in efficiency and regeneration capabilities, necessitating novel approaches to water treatment. The primary objective is synthesizing and characterizing high-quality ABC adsorbents capable of effectively removing MB. The activation process was optimized, and adsorbent performance was evaluated regarding MB removal efficiency and regeneration potential. Various activation dos-ages were investigated, and comprehensive physicochemical characterization was performed using scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), BET (Brunauer–Emmett–Teller) analysis, X-ray fluorescence (XRF), thermogravimetric analysis (TGA), and X-ray diffraction (XRD). The synthesized adsorbents demonstrated exceptional MB removal efficiency (99.593%) and impressive adsorption capacity (22.131 mg/g) when activated with 16 M sodium hydroxide. The adsorption process exhibited spontaneity and exothermicity, as validated by Freundlich and second-order kinetic models. Furthermore, the adsorbents showcased successful regeneration and reusability over three cycles, highlighting their potential for long-term application in water treatment. This study significantly advances water treatment by offering a novel approach to MB removal using base-activated bentonite clay (BABC) adsorbents, contributing to the development of sustainable water treatment solutions.